anonymous
  • anonymous
Y"+x^2y'+xy=0 power series
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
About \(x=0\)?
anonymous
  • anonymous
Yes
Jacob902
  • Jacob902
y = ∑(n=0 to ∞) a_n x^n y' = ∑(n=0 to ∞) a_n n x^(n-1) y'' = ∑(n=0 to ∞) a_n n(n-1) x^(n-2) y'' - x^2 y' - xy = = ∑(n=0 to ∞) a_n n(n-1) x^(n-2) - - ∑(n=0 to ∞) a_n n x^(n+1) - - ∑(n=0 to ∞) a_n x^(n+1) = = ∑(n=-1 to ∞) a_(n+3) (n+3)(n+2) x^(n+1) - - ∑(n=0 to ∞) a_n n x^(n+1) - - ∑(n=0 to ∞) a_n x^(n+1) = 0 The first sum starts at n=-1, the other two start at n=0. Then, the term n=-1 of the first sum must be zero: a_2 ∙ 2 ∙ 1 = 0 => a_2 = 0 For n≥0: a_(n+3) (n+3)(n+2) - a_n (n+1) = 0 => a_(n+3) = a_n (n+1) / [(n+3)(n+2)] It's right: you can choose a_0 and a_1 arbitrarily (order 2, 2 initial conditions to adjust), and a_2 must be zero. All other a_n are given by the previous recursion.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
\[\begin{align*} y&=\sum_{n=0}^\infty a_nx^n\\[1ex] y'&=\sum_{n=1}^\infty na_nx^{n-1}\\[1ex] y''&=\sum_{n=2}^\infty n(n-1)a_nx^{n-2} \end{align*}\] Substituting into the ODE: \[\begin{align*} 0&=\sum_{n=2}^\infty n(n-1)a_nx^{n-2}+x^2\sum_{n=1}^\infty na_nx^{n-1}+x\sum_{n=0}^\infty a_nx^n\\[2ex] &=\sum_{n=2}^\infty n(n-1)a_nx^{n-2}+\sum_{n=1}^\infty na_nx^{n+1}+\sum_{n=0}^\infty a_nx^{n+1}\\[2ex] &=\sum_{n+3=2}^\infty (n+3)(n+3-1)a_{n+3}x^{n+3-2}+\sum_{n=1}^\infty na_nx^{n+1}+\sum_{n=0}^\infty a_nx^{n+1}\\[2ex] &=\sum_{n=-1}^\infty (n+3)(n+2)a_{n+3}x^{n+1}+\sum_{n=1}^\infty na_nx^{n+1}+\sum_{n=0}^\infty a_nx^{n+1}\\[2ex] &=\left(2a_2+6a_3x+\sum_{n=1}^\infty (n+3)(n+2)a_{n+3}x^{n+1}\right)+\sum_{n=1}^\infty na_nx^{n+1}\\[1ex] &\quad\quad+\left(a_0x+\sum_{n=1}^\infty a_nx^{n+1}\right)\\[2ex] &=2a_2+(6a_3+a_0)x+\sum_{n=1}^\infty \bigg[(n+3)(n+2)a_{n+3}+(n+1)a_n\bigg]x^{n+1} \end{align*}\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.